Reducing the foot trajectory variabilities during walking through vibratory stimulation of the plantar surface of the foot - Shun Yamashita (Nature Portfolio, 2021)
Abstract Variabilities or fluctuations in foot clearance are considered as a risk factor for falls during walking in older adults. The present study aimed to investigate whether the foot trajectory variability can be reduced by applying vibratory stimulation to the foot's plantar surface during walking. Ten healthy adults were asked to walk on a treadmill with vibratory shoes, and body kinematics were measured. Changes in the mean absolute deviations of the foot trajectory and joint and trunk angles were compared between the periods of applied or absent vibratory stimulus. Our results demonstrated that toe trajectory variability in the swing phase was significantly smaller when a vibratory stimulus was applied. Applying vibratory stimulus to the soles of the forefoot could potentially be used to reduce foot trajectory variability, which could reduce the risk of trips and associated falls during walking in older adults.